How to keep farm accounts - Ngeze, P.B. (Acacia Stantex Publishers / CTA / Friends-of-the-Book Foundation, 2003)
Keeping accounts can pose a major challenge for farmers. This books aims to provide them with basic information on farm records and accounts. It covers types of farm records, steps to be followed in keeping farm records, banking services, using accounts in the context of a modern farm, and farm budgets.